Study of the influence of metro loads on the destruction of nearby buildings and construction structures using BIM technologies - Bashynskyi, Yaroslav; Barabash, Maria; Bieliatynskyi, Andrii (Journal of Civil Engineering and Management, 2023)
The authors studied the influence of metro loads on the destruction of nearby buildings and construction structures with the help of BIM technologies in order to eliminate the human factor at the design stage. In the study, numerical modeling was carried out using the LIRA-SAPR software package, and dynamic loadings were set by the time integration technique. The suggested technique involved a nonlinear dynamic analysis conducted considering the time factor; the parameters of the stress-strain state (displacement, force, stress) were determined at each moment of exposure, changing the rigid characteristics of the building structures. The authors conducted a structural assessment of an unfinished construction facility, considering the vibrodynamic loads of the metro. Numerous models were adopted as the structural designs of buildings that consider various impact factors, such as nonlinear soil behavior and permanent action and the nature of dynamic loads. The comparison with experimental data confirmed the theoretical and computational parts of the developed technique. The study determined the vibrodynamic impact of the metro on the construction structures. Verification of the developed methodology based on BIM technologies was carried out by comparing the results of numerical experiments with the results of subsequent full-scale vibration tests.